Productive Behavior of Varieties Plants of Strawberry (Fragaria x ananassa Duch.) by Date of Rooted in Northwest Uruguay - Barros Mainardi, Carlos; García De Souza, Margarita (Agrociencia Uruguay, 2015)
For three years, trials have been carried out in a commercial property in the area of Salto in order to determine the relationship of varietal characteristics with the early and total production potential of «direct container» local plants, rooted in different moments. The design used was randomized complete blocks with factorial arrangement, combining different varieties with three dates of rooting. The varieties responded differently in the precocity of fruit production to the dates of rooting. INIA Arazá responded positively to the advance in the rooting date, while the other varieties did not. However, in general, yied for late rooting plants was inferior to the early rooting ones, due to variations in the number of fruits. The average fruit size was mainly determined by genetic factors. For the full harvest period, yield showed no relationship between the rooting date and the variety. Camarosa and Earlibrite showed high yield potential, INIA Yvahé was intermediate, and Gaviota and INIA Arazá had the lowest yields. For early fruit production, seedlings from the beginning of the rooting period can be used as a suitable alternative, standardizing the beginning of the crop production.